2021
DOI: 10.1111/nmo.14167
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine before esophageal manometry and ambulatory pH monitoring: A randomized controlled trial

Abstract: Background: Lidocaine is commonly applied to improve the tolerance of esophageal manometry (EM) and ambulatory pH monitoring (PM). We recently published data suggesting a benefit to this practice and we aimed to confirm these findings in a randomized trial. Methods:We conducted a double-blind, randomized trial of lidocaine nasal spray versus placebo (saline) before EM and PM. Patients referred to our center who met inclusion criteria were enrolled. Patients were asked to fill a questionnaire after their test a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…The effect of lidocaine on pain management has been studied before, including in HRM, with mixed results. 25 A Cochrane review of eight randomized controlled trials concluded that topical anesthetic did not reduce pain or discomfort. 26 Researchers have suggested further investigation of topical anesthetic during transnasal manometry is indicated, as transnasal manometry is particularly painful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of lidocaine on pain management has been studied before, including in HRM, with mixed results. 25 A Cochrane review of eight randomized controlled trials concluded that topical anesthetic did not reduce pain or discomfort. 26 Researchers have suggested further investigation of topical anesthetic during transnasal manometry is indicated, as transnasal manometry is particularly painful.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, transnasal procedures are commonly performed in the awake patient and are known to be associated with pain. The effect of lidocaine on pain management has been studied before, including in HRM, with mixed results 25 . A Cochrane review of eight randomized controlled trials concluded that topical anesthetic did not reduce pain or discomfort 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Wahba and collaborators 7 reported that “Routine use of lidocaine before esophageal function tests does not reduce pain during catheter insertion.” They observed an OR = 0.758 (95% CI 0.467–1.228), which can be interpreted as a 24% reduction in the odds of occurrence of pain during catheter insertion, which patients may consider as an important result. For illustration purposes, if the exact same OR result had been obtained in a study three times as large ( n = 900 as opposed to n = 300 patients), one would have “achieved statistical significance” (see tables below) and would have probably stated “Routine use of lidocaine before esophageal function tests does reduce pain during catheter insertion.”…”
Section: Statistical Significance Is Unrelated To Clinical Importancementioning
confidence: 99%
“…Wahba and collaborators 7 reported that "Routine use of lidocaine before esophageal function tests does not reduce pain during catheter insertion." They observed an OR = 0.758 (95% CI 0.467-1.228), which can be interpreted as a 24% reduction in the odds of occurrence of pain during catheter insertion, which patients may consider as an important result.…”
Section: S Tatis Ti C Al S I G Nifi C An Ce Is Unrel Ated To Clini C ...mentioning
confidence: 99%
“…Most patients tolerate the examination (>95%) [ 29 ]. The catheter insertion may be associated with significant pain, and the pH probe may cause belching and coughing during the early part of the monitored period, especially in patients with esophageal or laryngopharyngeal mucosa hypersensitivity [ 29 , 30 ]. The pharyngeal probe placement difficulties and movements are both points that were frequently considered as weaknesses of the technique, leading to probe movement and false-positive diagnostic [ 29 , 31 ].…”
Section: Diagnosis Of Reflux and Place Of Ph Studymentioning
confidence: 99%